CONSTRUCTION OF THE MEANING OF POVERTY AND ADAPTATION STRATEGIES OF RICE FARMERS IN PAYARABO TIMU, NORTH ACEH - Nilawati; Nulwita Maliati; Mursyidin; Cut Rizka Al Usrah; Syamsuddin (Jurnal Transparansi Publik (JTP), 2026)
The research problem is the definition of poverty of rice farmers according to the community, the causes and efforts of rice farmers to overcome their poverty in Gampong Payarabo Timu. The theory used is the theory of poverty according to Selo Sumardjan which explains that poverty patterns are divided into four, namely relative, individual, cultural and structural poverty. The research method uses a qualitative approach, namely research that produces descriptive data regarding spoken and written words and observable behavior of the people studied. The results of the research show that the definition of poverty for rice farmers according to the community in Gampong Payarabo Timu is (a) The definition of poverty according to farmers who own land, namely low land ownership, (b) The definition of poverty according to farm workers, namely not having access to farming and irregular/odd jobs, (c) The definition of poverty according to land-renting farmers is a system of profit sharing (land rent) and land rent to fulfill basic needs. The causes of poverty among farmers in Gampong Payarabo Timu are (a) limited land ownership, (b) low income due to limited employment opportunities and (c) not having capital to farm. Farmers' efforts to overcome poverty in Gampong Payarabo Timu are (a) utilizing village rice field usage rights, (b) building trust in cooperation with land owners, (c) utilizing creativity through MSME activities and (d) working as casual daily laborers, (e) utilizing PKH assistance.